Petrogenetic re-examination of spinel + quartz assemblage in the Larsemann Hills, East Antarctica - Bose, Sankar; Mondal, Arnob Kumar; Bakshi, Ashok Kumar; Jose, Jis Romal (Polar Science, 2020)
We present textural evidence of spinel (low-Zn) and quartz from two samples of quartzofeldspathic rocks from the Larsemann Hills, East Antarctica. The present occurrence is unusual for the fact that the direct grain contact is preserved unlike most other occurrences where these two phases are separated by reaction products during retrograde and/or prograde metamorphic stages. Textural features further indicate that Ti-biotite was part of the prograde assemblage that underwent partial melting to produce spinel. The maximum temperature estimated from the rock is 870 °C. Monazite grains are abundant in the rock and these are mostly homogeneous in terms of U, Th and Pb distribution. In situ U–Th-total Pb EPMA data of these monazite yield a group age of 527 ± 8 Ma. Textural and geochronological data match with the second (M2) stage of metamorphism of the Larsemann Hills region as evident from the existing geological record. Although spinel and quartz was considered to be a part of peak M2 assemblage in earlier studies, preservation of their grain contact is enigmatic. We consider the grain contact metastable and its preservation possibly resulted from significant overstepping of cooling reaction due to fast reaction kinetics. journal article